2007
DOI: 10.1021/om0609822
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Aliphatic Ethers by TpMe2Ir Compounds:  Multiple C−H Bond Activation and C−C Bond Formation

Abstract: Benzene solutions of the unsaturated fragment TpMe2Ir(C6H5)2 (1), generated in situ from either TpMe2Ir(C2H4)2 or TpMe2Ir(C6H5)2(N2), react with methyl ethers MeOBut, MeOBun, and MeOCH2CH2OMe to give the organometallic hydride carbene products TpMe2(H)2(C(H)OR) 4 (R = But, 4a; Bun, 4b; CH2CH2OMe, 4c) along with benzylic ethers C6H5CH2OR 5. The overall reaction is very complex and involves the participation of two molecules of the ether, MeOR, and one of benzene per molecule of the iridium precursor. The latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 53 publications
3
19
0
3
Order By: Relevance
“…The carbonyl group‐containing organometallic intramolecular coordination five‐membered ring compounds prepared by orthometalation are shown in equation (4). Sixteen kinds of elements and 79 types of compounds are included in the Cambridge Structural Database 18–52. For example, the orthometalations of alkyl phenyl ketone [equation (5)29], aryl phenyl ketone [equation (6)36], benzaldehyde [equation (7)35], phenyl amide [equation (8)46], etc.…”
Section: Synthesis Of Carbonyl Group‐containing Organometallic Intrammentioning
confidence: 99%
“…The carbonyl group‐containing organometallic intramolecular coordination five‐membered ring compounds prepared by orthometalation are shown in equation (4). Sixteen kinds of elements and 79 types of compounds are included in the Cambridge Structural Database 18–52. For example, the orthometalations of alkyl phenyl ketone [equation (5)29], aryl phenyl ketone [equation (6)36], benzaldehyde [equation (7)35], phenyl amide [equation (8)46], etc.…”
Section: Synthesis Of Carbonyl Group‐containing Organometallic Intrammentioning
confidence: 99%
“…The following elimination of H 2 would afford the osmium carbene. With regard to this mechanism, we note that recently Carmona [9] and Grubbs [10] reported that the reactions of a bis(ethene) iridium(I) and a dihydrido iridium(III) complex with methyl ethers CH 3 OR (R = CMe 3 , CH 2 CH 2 CH 2 CH 3 , CH 2 CH 2 -OMe) produced Fischer-type iridium oxocarbenes in excellent yields. The authors proposed that the decisive step of these processes consists in the elimination of, respectively, C 2 H 4 and H 2 from the starting material and the formation of a coordinatively unsaturated iridium(I) intermediate to which the ether coordinates.…”
Section: Resultsmentioning
confidence: 88%
“…Die Alkoxymethylverbindungen [(Tp′)Ir(C 6 H 5 )(CH 2 OR)] können durch Zugabe von Acetonitril abgefangen werden und liefern so die 1:1‐Addukte [(Tp′)Ir(C 6 H 5 )(CH 2 OR)(NCMe)], die bei thermischer Zersetzung die Monohydrido(oxocarben)‐Komplexe [(Tp′)IrH(C 6 H 5 ){C(H)OR}] bilden. Beim Erwärmen von Lösungen der Komplexe [(Tp′)IrH(C 6 H 5 ){C(H)OR}] (R= n ‐C 4 H 9 oder CH 2 CH 2 OMe) in Cyclohexan auf 80 °C entstehen nach C‐H‐Bindungsspaltung und C‐C‐Verknüpfung die Aryl(hydrido)‐Verbindungen [(Tp′)IrH{κ 2 ( C , O )‐C 6 H 4 CH 2 OR}], die spektroskopisch und im Fall von R= n ‐C 4 H 9 durch eine Kristallstrukturanalyse charakterisiert wurden 40b. Der Dihydridokomplex 49 b reagiert in einem Gemisch von Benzol und Methyl( n ‐butyl)ether bei 100 °C zu der Hydrido( n ‐propyl)carbonylverbindung 50 .…”
Section: Acyclische Ether Und Tertiäre Amine Als Substrateunclassified
“…Der Dihydridokomplex 49 b reagiert in einem Gemisch von Benzol und Methyl( n ‐butyl)ether bei 100 °C zu der Hydrido( n ‐propyl)carbonylverbindung 50 . Dieses ist eine ungewöhnliche Reaktion insofern, als die Spaltung einer CH 3 ‐OR‐Bindung im Allgemeinen energetisch schwieriger als die Aktivierung einer C‐H‐Bindung ist 40b…”
Section: Acyclische Ether Und Tertiäre Amine Als Substrateunclassified
See 1 more Smart Citation